Software maintenance in Argentina: 2001 status - Silberman, Alan (2002)
In the following communication the result of a survey exploring the software maintenance status in Argentina is presented. Responses describing major problems and preferred changes in MIS organizations were classified into general categories and compared with previous similar studies. Important questions regarding effort allocation and other decisions regarding maintenance activities are analyzed, generating possible explanations for the current status of maintenance practices in Argentina.